Liderança, administração e gestão nos cuidados de saúde: um protocolo de revisão de escopo no âmbito do ensino da enfermagem - Estefania Coello Gonçalves Canedo; Carla Silvia Fernandes; Maria Manuela Ferreira Pereira da Silva Martins (Instituto Politécnico de Viseu, 2023)
Introduction: Strategic leadership in nursing, represents one of the global goals at the current time. Although integrated into university programs, the teaching of administration and management, did not seem to promote the expected results. This finding may be a consequence of the teaching methods, competencies targeted, or students' perceptions of the usefulness and interest of the subject. A new theoretical framework is needed, with the identification of underpinning skills, key contents and teaching methodologies adapted to the current reality. Objectives: Map the models and conceptions of teaching-learning nursing administration and management. Methods: This review will follow the JBI methodology, and will include all types of studies, published in English, French, Spanish, and Portuguese, on the last decade, without any geographical limitations. The databases included MEDLINE, CINAHL, Psychology and Behavioral Sciences Collection by EBSCO, Scopus (Elsevier), Canadian Science Publishing, grey literature (Google Scholar) and Repositório Científico de Acesso Aberto de Portugal (RCAAP). Data will be analysed and extracted by two independent researchers and will be presented in a specific table. Results: Previous bibliographic research allowed the identification of some concepts, theories and pedagogical strategies implemented in the teaching-learning process of the subject. Conclusion: The results will contribute to help instructors to improve their educational approach, adapting the theory of the subject through the use and development of teaching-learning strategies that can support and empower upcoming nurses, face to future challenges in healthcare. Keywords: leadership; learning; nursing education; nursing management; nursing student